Tsunami Evacuation Route Mapping in the Tegalkamulyan Area, Cilacap Regency, Based on the Potential of a South Java Earthquake - Saputri, Aliffia Retno Maya; Muqoddas, Muhamad Mahfud; Irayani, Zaroh (Jurnal Meteorologi dan Geofisika, 2025)
Cilacap Regency is one of Indonesia’s rapidly developing regions, particularly in the oil mining industry, but it is also highly vulnerable to tsunami hazards due to its location along the South Java subduction zone. A major tsunami generated by a large earthquake in this zone would severely impact coastal areas, including the Tegalkamulyan area. As part of disaster mitigation efforts, this study conducted tsunami evacuation route mapping using tsunami wave propagation modeling based on the Shallow Water Equations (SWE). The simulations employed three hypothetical South Java earthquake sources proposed by the National Earthquake Study Center in 2017, with magnitudes up to Mw 8.7. Among these, Scenario 5 represents the worst-case scenario, producing the largest vertical displacement, with a wave uplift of 11.418 m and a subsidence of −7.476 m. The results show that tsunami waves propagate in all directions, with the fastest arrival time reaching the coast 44 minutes and 1 second after the earthquake. The maximum inundation distance extends up to 12.7 km from the coastline, covering an area of 534.890 km², with a maximum run-up height of 30.847 m. Based on the evacuation route mapping, vertical evacuation directs residents to seek tall buildings or Temporary Evacuation Sites within approximately 6–23 minutes on foot, while horizontal evacuation routes guide evacuees from Temporary Evacuation Sites to Final Evacuation Sites within approximately 13–20 minutes using motorized vehicles at an average speed of 38 km/h.